"Finding Something for Bénédicte to Do": What Place can Women with Learning Difficulties Have in the Eucharistic Liturgy? - Cooreman-Guittin, Talitha (Concilium, 2020)
In the last few years Pope Francis has frequently appealed for people living with disabilities to be allowed to take their full place in the Church, especially in catechesis and liturgy. Nevertheless we are finding that it is not always easy to find an appropriate place suitable for everyone. The place of women with learning difficulties in the Eucharist has not really been given much thought. This article sets out to examine the possibility that a woman with learning difficulties could act as an acolyte in the Eucharistic liturgy.